2004
DOI: 10.5326/0400029
|View full text |Cite
|
Sign up to set email alerts
|

Topical 0.1% Tacrolimus for the Treatment of Discoid Lupus Erythematosus and Pemphigus Erythematosus in Dogs

Abstract: Topical 0.1% tacrolimus was used for treatment of localized lesions associated with 10 cases of discoid lupus erythematosus (DLE) and two cases of pemphigus erythematosus (PE) either as a sole therapy (n=2) or as an adjunctive treatment (n=10). Eight of 10 dogs with DLE and both dogs with PE were improved following 8 weeks of topical application. In six of the eight dogs that improved, other medications were discontinued. No adverse effects in clinical or laboratory parameters were noted throughout the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
0
30
1
2
Order By: Relevance
“…Undetectable tacrolimus blood concentrations were in accordance with the hypothesis of this study. False positive results in control dogs or at baseline, previously reported with the IMx Tacrolimus MEIA (Abbott Laboratories, Abbott Park, IL, USA) in dogs, 17 were not encountered in the present study. The dose of tacrolimus applied in the present study was not expected to produce toxic blood concentrations (> 20 ng/mL), because it was lower than the doses applied in the two canine trials in which the average tacrolimus blood concentrations were below toxic levels 13,14 .…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Undetectable tacrolimus blood concentrations were in accordance with the hypothesis of this study. False positive results in control dogs or at baseline, previously reported with the IMx Tacrolimus MEIA (Abbott Laboratories, Abbott Park, IL, USA) in dogs, 17 were not encountered in the present study. The dose of tacrolimus applied in the present study was not expected to produce toxic blood concentrations (> 20 ng/mL), because it was lower than the doses applied in the two canine trials in which the average tacrolimus blood concentrations were below toxic levels 13,14 .…”
Section: Discussioncontrasting
confidence: 46%
“…Tacrolimus blood concentrations are usually low or undetectable in people, and there is no demonstrable effect of topical tacrolimus on other laboratory values 12 . One attempt to measure blood concentrations in dogs being treated with topical tacrolimus could not be interpreted due to false positive results from control animals 17 . In two other studies, most tacrolimus blood concentrations were below potentially toxic levels and no dogs showed any adverse reactions or had any changes in hematologic or biochemical parameters during the course of topical tacrolimus therapy 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported cardiac vasculitis, myocardial necrosis, pancreatic acinar cell degeneration, vacuolation of the renal proximal tubules, and centrilobular hepatocellular swelling 48,49 . Topical administration of tacrolimus however, has been used successfully for immunologic skin disorders such as perianal fistulas, discoid lupus erythematosus, pemphigus erythematosus, and atopic dermatitis, without significant systemic absorption 50–52 . Therapeutic ranges for tacrolimus have not been well established in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…This small retrospective case series suggests that oral or topical CIs represent an effective therapeutic option with minimal long‐term adverse effects for dogs with VCLE. Because they are potent T‐cell inhibitors, ciclosporin and tacrolimus have been used successfully for treatment of several canine CLE variants, such as exfoliative CLE (ECLE), mucocutaneous lupus erythematosus (MCLE), and localized and generalized discoid lupus erythematous (DLE) . The dosage of ciclosporin used in the present study (5.0–10.0 mg/kg) mirrored those administered in dogs with generalized DLE and ECLE .…”
Section: Discussionmentioning
confidence: 99%